The Comparision of Classical Ethical Theories in Ancient Greece Philosophy and Islamic Philosophy: The Example of Aristotle and Ibn Miskavayh, Tusi and Kinalizade - Öztürk, Emine (European Journal of Multidisciplinary Studies, 2021)
In this study, I will make an analysis of the comparision of classical ethical theories in Ancient Greece Philosophy and Islamic Philosophy. The analysis of the comparision of classical ethical theories in Ancient Greece Philosophy and Islamic Philosophy depends on three philosophical and psychological concepts. These concepts are first of all, the thought in other words the ability of thinking, secondly the desire, in other words the ability of desire, as Freud said libido, and thirdly agression the ability of anger. These three abilities in one person reveals one virtue in society, this virtue is the virtue of justice. And this study will tells about how we can reveal the virtue of justice in one society by applying these three abilities and virtues in one person. Because these abilties corresponds three virtues in classical ethics. These three virtues are thinking, chastity and courage. And this study will analyze the thinking, chastity and courage in Ancient Greece Philosophy and Islamic Philosophy.
Keywords: Comparision, Classical Ethics, Theories, Ancient Greece Philosophy, Islamic Philosophy